Transfer of European Union priority polycyclic aromatic hydrocarbons to lycopene extracted from tomato peel powder and assessment of the risks posed. (30th September 2021) - Wu, Naiying; Gao, Wei; Yang, Qingshan; Qiao, Xuanxuan; Cai, Yayuan; Gong, Junbo
Highlights: PAH can be sorbed by tomato peel and transferred to lycopene products. The crystallization process efficiently removed PAH 4 from purified lycopene. PAH 4 in lycopene are of low concern in terms of consuming lycopene microcapsules. Abstract: Tomato peel is a promising source of lycopene. Benzo(a)pyrene, benzo(a)anthracene, benzo(b)fluoranthene, and chrysene (PAH 4) are polycyclic aromatic hydrocarbons (PAHs) classed as priority pollutants by the European Union that can be sorbed by tomato peel and transferred to lycopene products. Here, the transfer of PAH 4 to extracted lycopene was assessed. Between 77.69% and 102.99% of PAH 4 in tomato peel was transferred to tomato oleoresin. The PAH transfer rate was closely related to the log (octanol–water partition coefficient). PAH partitioning depended on the PAH solubility in the different phases used. Only 0.028%–0.058% of the PAHs entered lycopene crystals, the rest remaining in the residue. This indicated that crystallization efficiently excluded PAH 4. Lycopene crystals 96.71% pure were produced that could be used in various commercial products. An exposure and risk assessment indicated that PAH 4 in lycopene do not pose strong risks to people consuming lycopene microcapsules.